Integrating Sports Psychiatry into Routine Athletic Care, Enhancing Athlete Performance and Well-being : A Systematic Review - Azzahra , Naila Ausshafa; Billa , Angel Salsa; Dika , Astia; Awalludin, Muchammad Rizky; Ridlowi , Dhani Achmad; Yani, Eli Dwi; Habibulloh , Firdaus Noval; Khumairah , Nessya (Health Frontiers: Multidisciplinary Journal for Health Professionals, 2024)
The integration of sports psychiatry into routine athletic care is essential for improving athlete performance and well-being. Athletes are susceptible to mental health issues such as depression, anxiety, ADHD, and eating disorders, which can negatively impact their performance. This study reviews existing research on sports psychiatry's role in enhancing mental health and performance, utilizing a systematic approach to explore key psychiatric interventions. Methodologically, the review involved analyzing studies that assess the effectiveness of techniques like cognitive behavioral therapy, biofeedback, and mindfulness-based interventions in improving athlete outcomes. Main findings indicate that addressing mental health conditions through sports psychiatry enhances focus, resilience, and emotional control, contributing to better performance under competitive stress. However, challenges such as stigma and the need for individualized care persist. The principal conclusion is that integrating sports psychiatry into athletic care improves both mental health and performance, with future research needed to explore long-term effects and personalized interventions.